(untitled) - Okakura-Kakuzo (New York, 1904)
Okakura Kakuzō (1862 – 1913), the author of The Book of Tea, was a Japanese scholar who contributed to the artistic development of his native country.
Keywords: Japan,Nhật Bản; History,Lịch sử